Program Pencegahan Kekerasan Seksual pada Remaja: Scoping Review: Sexual Abuse of Adolescents’ Prevention Program:Scoping Review - Solehati, Tetti; Cecep Eli Kosasih; Ade Kirana; Anita Purnama; Dea Aulia Putri; Lidya Nazhifa Kusumah; Kinaya Vathia Zalva Niara; Nadila Vinri; Rizka Fauzia Rahmah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2025)
Sexual abuse of adolescents is a serious global problem and a challenge for all countries because it can cause negative physical and psychological impacts on victims. Efforts to prevent sexual abuse of adolescents are needed to reduce the incidence of abuse of adolescents. to map the sexual abuse of adolescents’ prevention program. Research method: Scoping review research design. Article search using keywords from MeSH assisted by the Scopus, PubMed, and Springer databases based on inclusion criteria such as: in English, full text published between 2014-2024, topics about sexual abuse of adolescents are primary articles with experimental research designs, clinical trials, RCTs, quasi-experiments, and pre-experiments. The initial search found 318,227 articles. After screening, eight eligible articles were found, with eight sexual abuse of adolescents’ prevention intervention programs that affect the prevention of sexual abuse in dating physically and psychologically, sexual abuse, and adolescent skills in accessing information related to sexual health and communication. The adolescent’s prevention has been proven to be effective in preventing sexual abuse. However, based on the findings, there are still minimal studies on preventing sexual abuse of adolescents in Indonesia; therefore, it is recommended that further research be conducted on the application of forms of interventions to prevent adolescent sexual violence in Indonesia. ABSTRAK Kekerasan seksual pada remaja (KSR) merupakan masalah global yang serius dan menjadi tantangan bagi semua negara karena dapat menimbulkan dampak negatif fisik dan psikologis pada korbannya. Diperlukan usaha pencegahan KSR untuk mengurangi kejadian KSR. Untuk memetakan program pencegahan KSR. Desain penelitian scoping review. Pencarian artikel menggunakan kata kunci dari MeSH yang dibantu database Scopus, PUBMED, dan Springer berdasarkan kriteria inklusi seperti: berbahasa Inggris, fullteks yang diterbitkan antara tahun 2014-2024, topik tentang KSR merupakan artikel primer dengan desain penelitian experimental, clinical trial, RCT, quasi experiment, pra eksperimen. Pencarian awal ditemukan 318.227 artikel. Setelah dilakukan screening, ditemukan delapan artikel eligible, dengan delapan program intervensi pencegahan KSR yang mempengaruhi pencegahan kekerasan seksual dalam pacaran secara fisik dan psikologis, kekerasan seksual, serta keterampilan remaja dalam mengakses informasi terkait kesehatan seksual dan komunikasi. Program pencegahan KSR yang terbukti efektif mencegah KSR. Namun, dari hasil temuan masih minim studi pencegahan KSR di Indonesia, oleh karena itu disarankan untuk penelitian selanjutnya melakukan penelitian tentang penerapan bentuk intervensi pencegahan kekerasan seksual remaja di Indonesia.